Combustion behavior and slagging tendencies of kaolin additivated agricultural pellets and of wood-straw pellet blends in a small-scale boiler. (June 2019) - Mack, Robert; Kuptz, Daniel; Schön, Claudia; Hartmann, Hans
Abstract: The aim of this study was the modification of agricultural biofuels to allow for low emission combustion in domestic biomass boilers without slagging or other ash related problems. Four agricultural biomasses were additivated with kaolin. Fuel blends were produced from wheat straw and woody biomass. All fuels were combusted in a 30 kW biomass boiler while emissions and slag formation were measured. Due to additivation or fuel blending, total particle and CO emissions were reduced by 53–77% and 69–95%, respectively. At the same time, slag formation (determined as the mass of agglomerates > 3.15 mm) strongly declined. For fuels containing high amounts of sulphur or chlorine, kaolin additivation may lead to increased HCl and SOx emissions. Moreover, NOx -formation may be higher during combustion of additivated fuels (up to 21%). Overall, additivation with kaolin or blending of fuels might be an interesting option for the utilization of agricultural biomasses. The selection of the optimal upgrading method should consider the chemical and physical biomass properties and address the minimum amount of additive or blending ratio to achieve a sufficient reduction of emissions and slagging. Highlights: The effect of additivation with kaolin and blending on emissions and slagging was tested in a small scale boiler. 4 different fuels with a unique matrix of chemical composition were tested for the effect of additivation. Additivation could be an option to largely decrease particle and CO emissions and the risk of slagging during combustion. Some gaseous emissions (HCl, SOx, and NOx ) could be increased by additivation with kaolin. Fuel blending could be an alternative to additivation, but it's more effective on emission than on slag reduction.